oprC Impairs Host Defense by Increasing the Quorum-Sensing-Mediated Virulence of Pseudomonas aeruginosa - Gao, Pan; Guo, Kai; Pu, Qinqin; Wang, Zhihan; Lin, Ping; Qin, Shugang; Khan, Nadeem; Hur, Junguk; Liang, Haihua; Wu, Min (Frontiers in Immunology, 2020)
Pseudomonas aeruginosa, found widely in the wild, causes infections in the lungs and several other organs in healthy people but more often in immunocompromised individuals. P. aeruginosa infection leads to inflammasome assembly, pyroptosis, and cytokine release in the host. OprC is one of the bacterial porins abundant in the outer membrane vesicles responsible for channel-forming and copper binding. Recent research has revealed that OprC transports copper, an essential trace element involved in various physiological processes, into bacteria during copper deficiency. Here, we found that oprC deletion severely impaired bacterial motility and quorum-sensing systems, as well as lowered levels of lipopolysaccharide and pyocyanin in P. aeruginosa. In addition, oprC deficiency impeded the stimulation of TLR2 and TLR4 and inflammasome activation, resulting in decreases in proinflammatory cytokines and improved disease phenotypes, such as attenuated bacterial loads, lowered lung barrier damage, and longer mouse survival. Moreover, oprC deficiency significantly alleviated pyroptosis in macrophages. Mechanistically, oprC gene may impact quorum-sensing systems in P. aeruginosa to alter pyroptosis and inflammatory responses in cells and mice through the STAT3/NF-κB signaling pathway. Our findings characterize OprC as a critical virulence regulator, providing the groundwork for further dissection of the pathogenic mechanism of OprC as a potential therapeutic target of P. aeruginosa.